Persistencia campesina en espacios revalorizados por el capital: Un análisis integrado del metabolismo de ruralidades emergentes en los recintos La Cruz, Guarumal y Maculillo del cantón Mocache, provincia de Los Ríos - Meza Riera, Rubén (2017)
The present investigation was developed in the La Cruz, Guarumal and Maculillo precincts belonging to the Mocache canton, province of Los Ríos. The investigative work lasted four months. This research is mixed since it combines both qualitative and quantitative information, developed in its fullness in the field. The information gathered through surveys and focus groups were experiences that made possible the correct synthesis of information and its interpretation, all this in view of the need to make rural life visible and to know its metabolisms and subsistence strategies. The research work allowed to collect data mainly on: a) the socio-economic characteristics of the family units, b) land uses and amount of available land and c) characterization of the activities in which the time is allocated, which is why it is framed within a non-experimental design, identifying and characterizing the metabolism of two main peasant typologies of the study area multi-dimensionally. These typologies are the following: farmers with cocoa cultivation associated with fruit trees and corn monoculture, and the second typology, semi-proletariat farmers. The main results are: typologies 1 and 2 present average ages of heads of households between 44.38 and 46.67 years for both men and women, with 4.18 and 2.80 active members per household for typologies 1 and 2 respectively. Heads of household of typology 1 dedicate 8.15 daily hours to domestic work, while female heads of household of typology 2 dedicate 4.18 daily hours to domestic chores, that is 50% less with respect to typology 1 , whose average productive units are 4.88 ha, while the average productive units of typology 2 are 2.83 ha, significant differences that force both the head of the household to sell their labor force to complete the income for keep the home In the economic dimension there are marked differences between the two types with respect to income from the sale of agricultural products, where the values obtained by households of typology 1 duplicate those registered in households of typology 2. However, agricultural labor productivity ($ / ha) of typology 2 significantly exceeds that obtained by typology 1, due to the number of working hours by peasants of this typology.